Incidence of cancer-related lymphoedema: a protocol for a living systematic review with meta-analysis - Nele Devoogdt; Hildegard Reul-Hirche; Kira Bloomquist; Michael Bernas; Ben Singh; Sandi Hayes; Melanie Plinsinga; Debbie Geyer; Louise Koelmeyer; Neil Piller; Stanley Rockson (BMJ Open)
Introduction Given the projected rise in the incidence of cancer treatment-related conditions, such as lymphoedema, and the limited research on lymphoedema in cancers with poor prognoses, there is a need for a better understanding of cancer-related lymphoedema incidence and associated risk factors across all types of cancers. The objectives of this review are (1) to produce a resource on an open-access platform that facilitates continuous update of incidence estimates and risk factors as evidence emerges, (2) to provide the most up-to-date estimate of the incidence of cancer-related lymphoedema and (3) to evaluate the strength and consistency of the association between lymphoedema and cancer treatment and non-treatment-related risk factors.Methods and analysis A living systematic and grey literature search will be conducted to identify studies reporting the incidence, prevalence of lymphoedema or associated risk factors in individuals who have undergone treatment for any type of cancer. Two investigators will independently extract data and assess the risk of bias using the Cochrane Risk of Bias Tool Version 2.0, the Risk of Bias in Non-randomised Studies – of Interventions or the National Institutes of Health Heart, Lung and Blood Institute Study Quality Assessment Tools, depending on study design. The overall strength of evidence will be appraised with the Grading of Recommendations, Assessment, Development and Evaluations tool. Random effect models will be used to produce pooled overall lymphoedema incidence estimates. Subgroup analyses that explore relationships between lymphoedema incidence and lymphoedema measurement method, time since cancer diagnosis and treatment and diagnosis, treatment and behavioural characteristics will be conducted dependent on available data.Ethics and dissemination This living systematic review enables clinicians and researchers to consult a contemporary, comprehensive overview of the incidence of cancer-related lymphoedema and the association between lymphoedema and treatment and non-treatment-related risk factors.PROSPERO registration number CRD42022333291.